Ethyl Lactate as a Green Solvent in Terms of Sustainability and Economic Perspectives in Organic Synthesis Esterification: A Review - Hidayat, Abian Hilmi; Laksana, Mochamad Brian; Zakariya, Zulfa (Jurnal Beta Kimia, 2026)
This study presents a comprehensive analysis of ethyl lactate as a sustainable green solvent in organic synthesis, with a focus on feedstock evaluation and economic feasibility. A systematic literature-based approach was employed, covering publications from 2020 to 2025, and assessing two key aspects: (i) the source and cost of feedstocks, including whey, sugarcane molasses, rice straw, and starch, and (ii) the performance of ethyl lactate in various organic transformations. Techno-economic analysis estimates the cost of production (CoP) of ethyl lactate from sugarcane molasses in the range of USD 1,300-1,500/ton, while production from rice straw is estimated at around USD 5,600/ton, highlighting the economic advantage of molasses-based routes. Ethyl lactate has also demonstrated high effectiveness, achieving yields of 90-95% in various reactions such as coupling, metathesis, and ester synthesis. These findings reinforce the potential of ethyl lactate to support the chemical industry's transition toward more environmentally friendly processes, offering a compelling combination of technical performance and economic viability.